2022
DOI: 10.54783/ijsoc.v4i1.433
|View full text |Cite
|
Sign up to set email alerts
|

Learning Organization Strategy in the Face of Covid-19 with The Fifth Discipline Approach

Abstract: This study aimed to determine the strategies of learning organizations in dealing with the Covid-19 pandemic. This study uses a post-positivism approach with qualitative methods. Data was collected through in-depth interviews with informants from four companies analyzed online. Based on the data and analysis results, it can be concluded that the company has demonstrated the application of several disciplines from the fifth discipline approach. These four organizations have not fully implemented the five discip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In educational investigations, this method has been generally used [67]. Affording to journalism, there are two periods for the PLS path modeling approach: the measurement model and the structural model [68].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In educational investigations, this method has been generally used [67]. Affording to journalism, there are two periods for the PLS path modeling approach: the measurement model and the structural model [68].…”
Section: Resultsmentioning
confidence: 99%
“…Organizational learning of problems can be enhanced throughout HRD practices when the methods of HRD are applied as crucial reasons in managerial knowledge. Learning from crises is a mechanism to intensify executive resilience and improve the ability to absorb and formulate for future events; it also ensures the detection and correction of errors [68]. Organizations should increasingly establish agreements and enterprises with each other, academies, and governments to offer services such as preparation and development, crisis counseling, and developing portable benefits and other structures essential to nurture the staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forecasts made in 2019 and earlier have failed to materialize. In 2020, a substantial 85.83% of e-commerce businesses experienced a decline in revenue due to an 85.1% reduction in transaction volume (Yulivan & Anriani, 2022). Concurrently, Boudet et al (2020) research revealed that the pandemic has challenged customer loyalty.…”
Section: Introductionmentioning
confidence: 99%